2019
DOI: 10.31235/osf.io/dc5gh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Crafting Mosaics: Person-Centered Religious Influence and Selection in Adolescent Friendships

Abstract: This research addresses the intersection of two key domains of adolescents' lives: religion and peer networks. Religion scholars have argued that religion is multi-faceted and hence better understood by focusing on combinations of indicators (i.e. mosaics), versus a more traditional variable-centered approach. We adopt this framework and investigate the interplay between religion and peer networks, both in how religious mosaics are shaped by friends and how profiles affect friend selection dynamics. With data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 47 publications
0
7
1
Order By: Relevance
“…The conclusion, however, that religion rather than religiosity shapes youths’ friendship choices contrasts with findings from studies in the United States that found evidence of friendship selection on religiosity (Adams, Schaefer, and Ettekal 2020; Cheadle and Schwadel 2012; Cook, Schwadel, and Cheadle 2017). Because these studies examined youths that were older than those in our sample, developmental differences are one possible explanation for diverging findings because younger youths may be less able than older ones to accurately observe their peers’ religiosity.…”
Section: Discussioncontrasting
confidence: 95%
“…The conclusion, however, that religion rather than religiosity shapes youths’ friendship choices contrasts with findings from studies in the United States that found evidence of friendship selection on religiosity (Adams, Schaefer, and Ettekal 2020; Cheadle and Schwadel 2012; Cook, Schwadel, and Cheadle 2017). Because these studies examined youths that were older than those in our sample, developmental differences are one possible explanation for diverging findings because younger youths may be less able than older ones to accurately observe their peers’ religiosity.…”
Section: Discussioncontrasting
confidence: 95%
“…However, our results suggest such a shift can produce meaningful and useful results. As one of the first investigations of network selection and influence on clusters of behaviors (see also adams et al 2020), our approach complements existing strategies focused on individual behaviors. However, many mechanisms underpinning social influence may work equally well for clusters of behaviors as for individual behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The SABM behavior objective function predicts changes in individuals’ behavior as a product of their own attributes, others’ attributes (i.e., influence), and network structural features. SABMs have most often been used to model change in a single dichotomous or ordinal behavioral variable (Steglich et al 2010); however, they can accommodate latent classes (adams et al 2020), such as our categorical health lifestyles. To accomplish this, we adopted the strategy for modeling “behavioral” variables within an SABM as a two-mode network (Snijders, Lomi, and Torló 2013), coding each adolescent as having a membership state for each of the classes (or categories of affiliation), with 1 coded for the assigned class and 0 coded for the other classes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations